Vitamin D Analogs Can Retard the Onset or Progression of Diabetic Kidney Disease: A Systematic Review - Uwaezuoke, Samuel N. (Frontiers in Clinical Diabetes and Healthcare, 2021)
Introduction: Previous studies have shown that vitamin D analogs (such as paricalcitol) can reduce albuminuria in patients with diabetes mellitus and retard the progression of diabetic kidney disease (DKD). Although a recent systematic review reported significant improvement of renal function in patients with DKD who received vitamin D or its analogs, study-driven data about their use in ameliorating DKD outcomes have continued to accumulate over the years. Aim: This paper aims to systematically review the contemporary evidence about the effectiveness of vitamin D its analogs in retarding the onset or progression of DKD. Methods: With appropriate descriptors, two electronic databases (PubMed and Google Scholar) were searched for articles published between 2015 and 2021 in the English language. Primary studies that fulfilled the inclusion criteria were selected; their titles and abstracts were screened, and duplicates were removed. Relevant data were retrieved from the final selected studies using a preconceived data-extraction form. Results: A total of eight studies (three randomized-controlled trials, one prospective study, and four cross-sectional studies) were reviewed. A total of 6,243 participants were investigated in the eight studies and comprised young adults, middle-aged adults, and the elderly with a male-gender predominance. One randomized controlled trial reported that paricalcitol significantly improved renal function in type 1 diabetes patients with renal impairment when combined with renin-angiotensin-aldosterone system (RAAS) blockers. A strong correlation between vitamin D deficiency and DKD risk was noted in the majority of the cross-sectional studies. High doses of cholecalciferol, given early in DKD, resulted in a significant reduction in disease prevalence. Conclusion: Paricalcitol may retard the onset or progression of DKD, especially if administered in combination with RAAS blockers. The association of vitamin D deficiency with DKD risk also lends credence to this therapeutic benefit. Future systematic reviews are still needed to strengthen the current evidence and reach a consensus about this therapeutic effect.